LIVING IN THE SHADOW OF THE PLAN: A SOCIO-LEGAL STUDY OF THE AKIT INDIGENOUS COMMUNITY IN JANGKANG VILLAGE - Tuah Kalti Takwa; Kingkel Panah Grossman; Arif Wicaksa; Siti Mawaddah Palamani; Sri Agustina Ratnawati; Ahmad Fuadi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The Indonesian government established the 2021–2025 National Action Plan for Human Rights (RANHAM) as a commitment to protect the rights of vulnerable groups, including indigenous communities. However, a significant gap often exists between national policies and the realities faced by these communities on the ground. This study investigates the implementation of RANHAM for the Akit indigenous people inANGKAng Village, Bengkalis, who face significant socio-economic and cultural vulnerabilities. Using an empirical legal research method with a socio-legal approach, this study collected primary data through in-depth interviews with village officials, community leaders, and members of the Akit community. The findings reveal a stark reality: the RANHAM policy has not been socialized at the local level. Government officials and the Akit community themselves are largely unaware of the plan's existence, resulting in a complete failure of implementation. As a result, the state's promise of protection remains a paper plan, with no concrete action taken to safeguard the Akit people's cultural identity or land rights. This research concludes that RANHAM has been ineffective inANGKAng Village due to a fundamental breakdown in communication and implementation between central and local governments, leaving the Akit community without the intended legal and social protections.